Pengaruh green supply chain management terhadap performa ekonomi dan organisasi pada UMKM industri makanan di Wonosobo Jawa Tengah - Chalarhena, Novinda; Hendayani, Ratih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
MSME production activities contribute significantly to environmental pollution due to the limited knowledge and use of the latest technology on health and environmental impacts. The implementation of green supply chain management will bring drastic changes in supply chain processes. The costs incurred will increase, including the costs of inventory, production, and transportation. This study aims to analyze the relationship of three different levels of variables from the implementation of green supply chain management. This study uses quantitative methods with multivariate analysis methods. Data processing is assisted using smartPLS software. Data were collected by distributing 100 online and offline questionnaires to respondents and using a Likert scale measurement scale. Institutional pressure has a significant effect on external green collaboration and internal green practices. Leadership has a positive effect on internal green practices, but has no relationship with external green collaboration. External factors have no significant effect on economic and organizational performance. However, internal factors have a significant effect on economic and organizational performance. This research helps food SMEs to make decisions in formulating strategies and provides knowledge on the application of green supply chain management from various organizational perspectives.